THE ROLE OF ELECTRONIC WORD OF MOUTH ON ONLINE SHOPPING INTENTION IN E-COMMERCE - Audina Farah Assifah; Sumadi Sumadi (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2021)
During Covid-19, consumers are more likely to shop online to avoid physical contact. Consumers are even getting used to shopping for basic needs online. Social distancing policies have encouraged the business sector to better leverage digital potential. This study aims to analyze the effect of electronic word of mouth (E-wom) on purchase intentions through e-commerce. Questionnaires were distributed to respondents online, and 205 samples were collected for analysis. The data were then analyzed using Exploratory Factor Analysis using SPSS and Structural Equation Modelling (SEM) using AMOS. The results of the study found that Ewom had a positive effect on online purchase intentions through e-commerce.